Presentation of an umbilical cord cyst with a surprising jet: a case report of a patent urachus - Svigos, John (F1000Research, 2013)
We report a baby with an unusual true umbilical cord cyst detected at 12 weeks gestation which as the pregnancy progressed became increasingly difficult to distinguish from a pseudocyst of the umbilical cord. Concern of the possibility of cord compression/cord accident led to an elective caesarean section being performed at 35+ week’s gestation with delivery of a healthy female infant weighing 2170g. At birth the cyst ruptured and the resultant thickened elongated cord was clamped accordingly. After the cord clamp fell off at 5 days post delivery an elongated umbilical stump was left behind from which a stream of urine surprisingly jetted out from the umbilicus each time the baby cried. A patent urachus was confirmed on ultrasound and the umbilical jet of urine resolved at 4 weeks post delivery after treatment of an Escherichia coli urinary tract infection. At 11 weeks post delivery a laparoscopic excision of the urachus was successfully performed. The baby, now 18 months of age, continues to thrive without incident.